2021
DOI: 10.5539/hes.v11n2p91
|View full text |Cite
|
Sign up to set email alerts
|

Digital Educational Computer Games Environments Supporting Education (DECGE-SE)

Abstract: The purposes of the research were 1) to design the Digital Educational Computer Games Environments Supporting Education (DECGE-SE) and 2) to evaluate the DECGE-SE. The research procedure was divided into two phases. The DECGE-SE as follows: (1) Learning: (1.1) Subject area, (1.2) Learning objectives/Player goals, (1.3) Learning Theories, (1.4) Platform and (1.5) Type of game; (2) Instruction: (2.1) Game Cycle and (2.2) Components for educational computer games online; (3) Outcomes and Impacts comprised four el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It is said that the use of educational computer games has effectively increased the variable of students' academic selfregulation. Comparison with previous results about the variable of academic resilience is consistent with the results of this research (Zimmerman and Schunk, 2001;Alt and Naamati-Schneider, 2021;Hirt et al, 2021;Jantakun and Jantakoon, 2021;Luo, 2021;Staller et al, 2021;Bransen et al, 2022;Raković et al, 2022). This study was found to be inconsistent in the variable of academic self-regulation (The reason for this inconsistency can be because, firstly, the game used in Soltanizadeh and Bazizadeh's research is an intellectual and action style game, and secondly, the statistical population of this research is the city of Isfahan, Iran).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is said that the use of educational computer games has effectively increased the variable of students' academic selfregulation. Comparison with previous results about the variable of academic resilience is consistent with the results of this research (Zimmerman and Schunk, 2001;Alt and Naamati-Schneider, 2021;Hirt et al, 2021;Jantakun and Jantakoon, 2021;Luo, 2021;Staller et al, 2021;Bransen et al, 2022;Raković et al, 2022). This study was found to be inconsistent in the variable of academic self-regulation (The reason for this inconsistency can be because, firstly, the game used in Soltanizadeh and Bazizadeh's research is an intellectual and action style game, and secondly, the statistical population of this research is the city of Isfahan, Iran).…”
Section: Discussionsupporting
confidence: 92%
“…It was not long before computers became a popular pastime among children, teens, and adults alike. In the early 1990s, the Internet provided a new way of offering games ( Jantakun and Jantakoon, 2021 ). Children and adults were able to play their favorite games online.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…AIEd's application is still a hot topic among academics. Artificial intelligence in education (AIED) has opened new avenues for developing more successful learning practices and improved technology-enhanced learning applications or environments (Jantakun & Jantakoon, 2021;Jantakoon et al, 2019). Most scholars and professionals in the fields of computers and education, on the other hand, continue to struggle to implement related practices or programs (Kay, 2012).…”
Section: Introductionmentioning
confidence: 99%